Characteristics of shea butter processing in Niger State, Nigeria (2020)
The study examined the characteristics of Shea Butter processing and factors associated with the output in Niger states, Nigeria. Two stage sampling procedure was used to select 315 respondents. Interview schedule was used in data collection. Data collected were analysed with percentages, Chi-square, the Pearson Product Moment Coefficient (PPMC) and simple regression model at α 0.05. The result revealed that the majority (80.6%) of the respondents used semi-mechanised method in processing Shea butter. The average unit price of Shea butter was N476.07K per Kilogramme, while the average income was N439,650.37K per annum. Processors had low level of accessibility to modern processing technologies (66.2%) and more than half (64.8%) of the processors were producing at low level. Lack of credit facilities and high cost of processing equipment were identified as severe constraint to Shea butter processing. There were significant relationship between level of education (χ²=11.18, p≤0.05), level of engagement (χ²=8.71, p≤0.05), income (r=0.819, p≤0.05) and accessibility to modern Shea butter processing technologies (r=0.164, p≤0.05) with level of Shea butter processing output. The major determinants of Shea butter processing output were income, household size, unit price and accessibility to modern processing technologies. Financial institutions should provide soft loans to Shea butter processors to acquire inputs and equipment. Similarly, government agencies should provide Shea butter processing equipment to the processors to improve access to the technologies that could lead to increase Shea butter production in Niger state.